New version of Universal modeling method for centrifugal compressors calculation development - Yu. B. Galerkin; A. A. Drozdov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Similarity theory principles are widely applied in gas dynamic design. But completely new solutions must be realized on a base of engineering approaches to predict performances. The math model of Universal modeling method is a sum of algebraic equations for calculation of head losses. Some Russian and foreign manufacturers realized several dozens of designed compressors with power up to 32 MW designed by Universal modeling method. The experience of programs application allowed to work out the directions of mathematical model development for the new, 9th version of Universal modeling method. For 3D impellers calculation quasi-three-dimensional approach is used. The flow parameters are calculated on 8 blade-to blade surfaces. A new loading factor model was applied. It determines characteristic by the angle of inclination and the value of the loading factor at zero flow rate. A new losses model in a vaneless diffuser based on the results of CFD calculations generalization is used. The new model allowed more accurate calculation of narrow vaneless diffusers as compared to the previous model. Identification of the new mathematical model by the characteristics of model tests of centrifugal compressor stages is made. The efficiency calculation accuracy was sufficient for the engineering method